Gemological Characteristics and Spectral Characteristics of Grossular from Mt. Bozhushan in Southeast Yunnan Province - Liu-Run-Xuan Chen; Qiu-Yun Song; Xiao-Qi Yang; Xian-Chao Chen; Ruo-Han Zuo; Xue-Long Liu; Shi-Tao Zhang; Long-Fei Gui; Jie-Hu Zhou; Bo-De Lu (Crystals)
Grossular, a widely recognized colored gemstone in the market, attains premium quality when exhibiting pale-toned orange-yellow to golden-yellow hues with high transparency. Recently, our research team identified abundant gem-grade grossular associated with skarn-type polymetallic deposits in the Mt.Bozhushan area. However, these grossular specimens are currently discarded as mining waste. To promote their sustainable utilization, we conducted a systematic sampling of Mt.Bozhushan grossular and performed comprehensive analyses including fundamental gemological testing, spectroscopic characterization, and compositional profiling through EPMA and LA-ICP-MS. This multidisciplinary approach aims to establish an objective valuation framework for Mt.Bozhushan-derived grossular. The compositional and spectral data obtained in this study provide critical theoretical foundations and technical references for developing the gemstone resources of southeastern Yunnan’s Mt.Bozhushan grossular while establishing an evaluative baseline for grossular specimens from other regional deposits.